Intercropping of young grapevines with native grasses for phytoremediation of Cu-contaminated soils. (February 2019) - De Conti, Lessandro; Ceretta, Carlos A.; Melo, George W.B.; Tiecher, Tadeu L.; Silva, Lincon O.S.; Garlet, Luana P.; Mimmo, Tanja; Cesco, Stefano; Brunetto, Gustavo
Abstract: Intercropping may be a strategy for phytoremediation of vineyard soils with high copper (Cu) content. The study aimed to evaluate the contribution of South American native grasses in limiting Cu availability and toxicity in soils grown with grapevines. The soil used in the experiment was collected in natural grassland with no history of cultivation. The samples were air-dried; acidity, P and K levels were corrected and samples were then incubated. We used three Cu levels - natural content (Dose 0) and the addition of 40 and 80 mg Cu kg −1 of soil (Dose 40 and 80). At each Cu dose, grapevine was grown in three cropping treatments: monocropping, intercropping with Paspalum plicatulum and intercropping with Axonopus affinis . In intercropping, two grass seedlings were transplanted into each experimental unit 35 days prior to the transplanting of the grapevines. The soil solution was sampled and ionic speciation was carried out. At 70 days after planting, we sampled the grapevines to determine dry matter, morphological parameters and nutrient concentration in the roots and shoots. Intercropping young grapevines with Paspalum plicatulum and Axonopus affinis was efficient in promoting the growth of young grapevines at moderate and low levels of Cu contamination by reducing Cu bioavailability. This indicates that maintaining native grasses in young vineyards is an effective strategy for phytoremediating Cu-contaminated soils and obtaining a grape production system with reduced interventions in the native environment, in addition to contributing to soil protection and nutrient cycling. Graphical abstract: Highlights: Heavy metal phytoremediation of vineyards by native cover crops. Intercropping decrease Cu +2 in soil solution of Cu-contaminated soils. Native plants contribute to soil conservation and nutrient cycling in vineyards.